Early-Life Stress Alters Synaptic Plasticity and mTOR Signaling: Correlation With Anxiety-Like and Cognition-Related Behavior - Wang, Anfeng; Zou, Xiaojuan; Wu, Jiajia; Ma, Qingyu; Yuan, Naijun; Ding, Fengmin; Li, Xiaojuan; Chen, Jiaxu (Frontiers in Genetics, 2020)
Early-life stress (ELS) predisposes individuals to psychiatric disorders, including anxiety and depression, and cognitive impairments later in life. However, the underlying molecular mechanisms are not completely understood. Developmental deficits in hippocampal synaptic plasticity are among the primary detrimental alterations in brain function induced by ELS. Impaired synaptic plasticity is usually accompanied by decreased synaptic proteins, such as postsynaptic density 95 (PSD95) and synaptophysin, which are important for synaptic function. The mTOR signaling pathway plays a vital role in regulating protein translation, and mTOR activation is functionally associated with synaptic protein synthesis. In the present study, we observed whether ELS impacts synaptic protein synthesis and mTOR signaling, which is involved in synaptic plasticity. Herein, we established a maternal separation (MS) and chronic restraint stress (CRS) model and evaluated anxiety-like behavior and cognitive function (e.g., learning and memory) in adulthood through behavioral examination and analyzed hippocampal expression levels of PSD95 and synaptophysin. To explore whether the mTOR signaling pathway was associated with ELS, we also examined the activity of mTOR and s6. The behavior tests indicated that maternally separated mice showed increased anxiety-like behavior and cognitive impairments. PSD95 and synaptophysin mRNA and protein expression levels were decreased in the hippocampus, and phosphorylated mTOR and phosphorylated s6 were significantly decreased in maternally separated mice vs. those not exposed to MS. Our data demonstrate that MS impairs synaptic plasticity and inhibits mTOR signaling, specifically via s6. Therefore, we speculate that ELS decreased synaptic plasticity via the inhibition of the mTOR pathway in the hippocampus, which may underlie vulnerability to stress and mental disorders in adulthood.